Knowledge, Attitudes and Interest of Evidence Based Practice among Physical Therapist Working in Pakistan: Evidence Based Practice among Physical Therapist - Amjad, Sameen; Musaddiq, Lyba; Tasneem, Sharjeel Tasneem; Kashif, Muhammad; Iftikhar, Ghousia; Arif, Nimra; Ghaffar, Tamjeed (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Evidence-Based Practice (EBP) is an approach that integrates the best available research evidence with clinical expertise and patient values to guide clinical decision-making. Objectives: To determine the knowledge, attitudes and interests towards Evidence-Based Practice (EBP) among physiotherapists in Pakistan. Methods: We surveyed 302 physical therapists working in Government and private settings in Pakistan via an online survey. The survey questionnaire encompassed four sections: (1) respondent characteristics; (2) knowledge of the principles of EBP as well as attitudes, interests, use and perceived efficacy of EBP. Data were analyzed using the SPSS version-23. Results: Overall 85% perceived EBP study is useful and necessary in PT clinical practice and 83% of respondents believed the importance of literature discoveries in regular practice and in improving the worth of patient care. Moreover, 77% showed interests to incorporate evidence increasingly in regular practice and 82% of participants were interested in seeking and enhancing proficiency to implement EBP in practice. Conclusions: Majority of physical therapists took part in this study held positive attitudes towards the role of EBP. Most participants were interested in incorporating their perceived roles in practice as a means of honing their skills